2004
DOI: 10.1523/jneurosci.2705-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Spiral Waves in Disinhibited Mammalian Neocortex

Abstract: Spiral waves are a basic feature of excitable systems. Although such waves have been observed in a variety of biological systems, they have not been observed in the mammalian cortex during neuronal activity. Here, we report stable rotating spiral waves in rat neocortical slices visualized by voltage-sensitive dye imaging. Tissue from the occipital cortex (visual) was sectioned parallel to cortical lamina to preserve horizontal connections in layers III-V (500-m-thick, ϳ4 ϫ 6 mm 2 ). In such tangential slices, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
298
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(308 citation statements)
references
References 35 publications
(41 reference statements)
9
298
0
1
Order By: Relevance
“…Most of these rhythms (at least in vertebrates) are generated by the coherent oscillations of many coupled neurons. Sometimes they are synchronous and in other cases they are organized into patterns such as waves (for example in the swimming pattern of the lamprey; Cohen et al 1992) or even rotating waves (in certain brain slice preparations; Huang et al 2004. ) Thus, one of the outstanding theoretical questions in our understanding of neural rhythms is how the coupling interacts with the intrinsic dynamics to generate these patterns of oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these rhythms (at least in vertebrates) are generated by the coherent oscillations of many coupled neurons. Sometimes they are synchronous and in other cases they are organized into patterns such as waves (for example in the swimming pattern of the lamprey; Cohen et al 1992) or even rotating waves (in certain brain slice preparations; Huang et al 2004. ) Thus, one of the outstanding theoretical questions in our understanding of neural rhythms is how the coupling interacts with the intrinsic dynamics to generate these patterns of oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…Travelling waves of activity are also of interest. Experimentally, these can be induced by stimulating pharmacologically treated neural tissue slices (Pinto & Ermentrout 2001a;Huang et al 2004); they have also been observed in several different areas of the cortex of awake animals, often when no stimulation 152…”
Section: Introductionmentioning
confidence: 99%
“…Stable rotating spiral waves in rat neocortical slices visualized by voltagesensitive dye imaging were found in experiments [6,7]. As noted in [6,7], spiral waves might serve as pacemakers for the emergent population to generate periodic activity in a nonoscillatory network without the need for individual cellular pacemakers. It is interesting to simulate and investigate the formation and breakup of spiral waves in networks of neurons with different topologies.…”
mentioning
confidence: 75%
“…breakup, channel noise, factor of synchronization, probability of long-range connection Collective electrical behaviors of neurons and oscillators in networks often have spatiotemporal patterns [1][2][3][4][5][6][7][8][9][10][11]. A spiral wave is one such spatial pattern and is often observed in excitable and oscillatory media.…”
mentioning
confidence: 99%